2011
DOI: 10.3109/13813455.2011.582875
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of multiple myeloma and the role of M-band detection on serum electrophoresis in a small developing country. A retrospective study

Abstract: The data showed that the SPE and bone biopsy are the important tools in the diagnosis of multiple myeloma in a small developing country.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
(30 reference statements)
2
3
0
Order By: Relevance
“…In our study, the male to female ratio was 1.7:1, whereas the sex ratio was 1.2:1, as was reported in their study by Col GS Copra et al, [10]. A slight male predominance was also found in the study which was conducted by Nayak B S et al, [16]. The disease manifested in the later ages in females than in the male patients.…”
Section: Discussionsupporting
confidence: 73%
“…In our study, the male to female ratio was 1.7:1, whereas the sex ratio was 1.2:1, as was reported in their study by Col GS Copra et al, [10]. A slight male predominance was also found in the study which was conducted by Nayak B S et al, [16]. The disease manifested in the later ages in females than in the male patients.…”
Section: Discussionsupporting
confidence: 73%
“…Raised serum IgG levels, decreased serum IgA and IgM levels and immunofixation analysis was found significant with increasing ISS staging (p value <0.05) in our study. Serum protein electrophoresis in our study showed presence of M band in 80.58% (p value <0.05) of cases with most common location is in gamma region (58.80%) (p value <0.05) similar to previous studies (26,27). The biclonal gammopathy was found in 6% of cases.…”
Section: Discussionsupporting
confidence: 88%
“…[14] Even the available studies pertains only to clinical modalities rather than diagnostic criteria and clinicopathological profile. [14,15] A series of cases with diagnostic modalities on this condition is seldom available . [15] In the present research study we performed an extensive analysis on Clinico-hematopathological profile, biochemical and radiological parameters where the clinical and diagnostic results correlated emphazing the role of Pathologist in picking up POEMS syndrome thereby aiding the Physician in starting prompt diagnosis.…”
Section: A-528mentioning
confidence: 99%
“…In the present study, all the cases exhibited cardiothoracic manifestation with altered hemodynamics and ocular pathology. The main reason attributed is hyper viscosity of the blood altering the flow path associated with increased concentration of immunoglobulins [15]. Researchers postulated the same reason as the underlying cause for skin lesions as well with super addition of altered immunological response.…”
Section: Monoclonal -M Protein Was Detectable In Variable Quantificatmentioning
confidence: 99%
See 1 more Smart Citation